2009
DOI: 10.1007/s10705-009-9262-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of farmer management strategies on spatial variability of soil fertility and crop nutrient uptake in contrasting agro-ecological zones in Zimbabwe

Abstract: Variability of soil fertility within, and across farms, poses a major challenge for increasing crop productivity in smallholder systems of subSaharan Africa. This study assessed the effect of farmers' resource endowment and nutrient management strategies on variability in soil fertility and plant nutrient uptake between different fields in Gokwe South (ave. rainfall *650 mm year -1 ; 16.3 persons km -2 ) and Murewa (ave. rainfall *850 mm year -1 ; 44.1 persons km -2 ) districts, Zimbabwe. In Murewa, resource-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 15 publications
5
21
0
Order By: Relevance
“…This observation is in agreement with those reported for other parts of Africa, e.g. by Haileslassie et al (2007), Masvaya et al (2009) andTittonell et al (2005b). Concentric rings of varying soil fertility around homesteads have been described to be typical of West Africa (Prudencio 1993).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This observation is in agreement with those reported for other parts of Africa, e.g. by Haileslassie et al (2007), Masvaya et al (2009) andTittonell et al (2005b). Concentric rings of varying soil fertility around homesteads have been described to be typical of West Africa (Prudencio 1993).…”
Section: Discussionsupporting
confidence: 94%
“…Variability in soil properties across landscape positions, land use types and even the micro-variability associated with manure applications within individual field plots has been widely documented in the region (Brouwer et al 1993;Gandah et al 2003;Maccarthy et al 2013;Ofori et al 2013). In particular, Prudencio (1993) described the effect of 'ring' management in smallholder villages in Burkina Faso and documented strong gradients of decreasing soil fertility with increasing distance from the village homesteads-a pattern that has also been described in other parts of sub-Saharan Africa (Masvaya et al 2009;Zingore et al 2007). Fields that receive greater annual inputs of organic and mineral fertilizers tend to exhibit better soil fertility indicators, notably the fields near the homesteads, which are also planted earlier and weeded more frequently (Tittonell et al 2005b).…”
Section: Introductionmentioning
confidence: 73%
“…In developing countries, the increasing prices of inorganic fertilizers coupled with growing concerns for sustaining soil productivity have led to renewed interest in the use of organic manures as fertility-restorer inputs (Mapfumo et al 2007;Ouedraogo et al 2007;Masvaya et al 2011). Manures are a vital resource not only for supplying plant nutrients but also for replenishing organic matter content of agricultural soils particularly in the tropics (Groot et al 2006;Materechera 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Poor soil fertility is the primary bio-physical constraint that results in poor yields (Sanchez, 2010). Next to the inherent variability of soils and their fertility, management decisions result in the development of strong fertility gradients (Giller et al, 2006Masvaya et al, 2010;Tittonell et al, , 2007aZingore et al, 2007b). These gradients are spatial patterns of soil fertility, resulting from inherent differences in parent material, position in the landscape and, above all, the preferential allocation of manure, compost, mineral fertilizers and labour on fields near the homesteads .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, differences between farms in resource endowments, and hence in access to nutrient resources, lead to different gradients (Masvaya et al, 2010). Zingore et al (2007a) showed that better-endowed farmers with ample access to manure, fertilizer and means of transporting manure have only slight fertility gradients, while farmers with a limited amount of manure or labour, preferentially allocate such resources to the fields and gardens around their homesteads, resulting in a strong decreasing gradient of SOC.…”
Section: Introductionmentioning
confidence: 99%